Visceral adiposity index is useful for evaluating obesity effect on erectile dysfunction. (2nd April 2019) - Akdemir, Alp Ozgur; Karabakan, Mehmet; Aktas, Binhan Kagan; Bozkurt, Aliseydi; Ozgur, Emrah Gokay; Akdogan, Nebil; Yarıs, Mehmet
Abstract: Studies show that erectile dysfunction (ED) is associated with obesity, and it has been shown that the possibility of developing sexual dysfunction in obese men is 30% higher compared to those with normal weight. Obesity is measured using various methods, for example waist circumference (WC) measurement or body mass index (BMI), but recently, visceral adiposity index (VAI) has also been utilised to better assess obesity and metabolic syndrome. In our study, the potential link between VAI and ED was investigated. The data of 176 patients who presented to the urology outpatient clinic with erection complaints were retrospectively screened. A control group was also established with 122 men without complaints of erectile dysfunction. The erectile functions of all participants were determined using the International Erectile Function Index‐5 (IIEF‐5) scoring. In addition, their serum fasting blood glucose, total testosterone (TT), triglyceride (TG), low‐density lipoprotein (LDL) cholesterol and high‐density lipoprotein (HDL) cholesterol levels were measured. The physical examination comprised the measurement of WC, height and weight, and BMI. The mean age of the participants was 58.7 ± 8.4 for the ED group and 57.1 ± 7.5 for the control group. The mean VAI was statistically significantly higher in the ED group (5.32 ± 2.77) compared to the control group (4.11 ± 1.93) ( p < 0.001). Since VAI contains both physical and metabolic parameters, our findings suggest that it discloses the effects of WC, BMI, HDL and TG more clearly. VAI is considered useful for the assessment of the effect of obesity on ED patients.